Perceraian Pada Masa Pandemi Covid-19 di Mahkamah Syar’iyah Lhokseumawe - Nanda Mauliza; Edi Yuhermansyah; Yenny Sri Wahyuni (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
The Corona virus has changed aspects of married life. Divorce is currently booming because of the Covid 19 virus. Divorce occurs due to several factors, in general the trigger for divorce cases to increase is due to the Covid-19 pandemic. Covid-19 has had a significant impact on all aspects of life, including the divorce application that occurred at the Lhokseumawe Syar'iyah Court. This study aims to determine and analyze the increase in divorce requests during the Covid-19 Pandemic at the Lhokseumawe Syar'iyah Court and the factors causing the divorce, as well as the judge's efforts to reduce the occurrence of divorces affected by Covid-19 at the Lhokseumawe Syar'iyah Court. This study uses a qualitative approach with the type of field research. While the data collected in the form of primary and secondary data, the data obtained using direct interview techniques and documentation. To make it easier to check the data, in checking the validity of the data, the researcher uses the triangulation method. From this research, the writer gets several conclusions. The results of the study found that during the Covid-19 pandemic divorce cases at the Lhokseumawe Syar'iyah Court experienced an increase, but the cause of the divorce could not be stated specifically the impact that occurred due to the Covid-19 pandemic or these causes had occurred before the pandemic. . Divorce cases during the COVID-19 pandemic were caused by several factors and the dominant factors were economic factors, there was no harmony or constant bickering resulting in domestic violence, leaving one side behind, as well as the judge's efforts to reduce divorces affected by COVID-19. 19 at the Lhokseumawe Syar'iyah Court, namely through mediation.